Princess Academy - Hale, Shannon (New York Bloomsbury Children's Books Distributed to the trade by Holtzbrinck Publishers, 2005)
While attending a strict academy for potential princesses with the other girls from her mountain village, fourteen-year-old Miri discovers unexpected talents and connections to her homeland.
Keywords: Princesses -- Fiction; Self-confidence -- Fiction; Telepathy -- Fiction; Mountains -- Fiction; Schools -- Fiction